2009
DOI: 10.1542/peds.2007-3608
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Blood Lead Levels and Blood Lead Testing Among US Children Aged 1 to 5 Years, 1988–2004

Abstract: Children's blood lead levels continue to decline in the United States, even in historically high-risk groups for lead poisoning. To maintain progress made and eliminate remaining disparities, efforts must continue to test children at high risk for lead poisoning, and identify and control sources of lead. Coordinated prevention strategies at national, state, and local levels will help achieve the goal of elimination of elevated blood lead levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
215
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(232 citation statements)
references
References 24 publications
15
215
2
Order By: Relevance
“…Similar findings have been found in other countries. [6,7,9] However, in Cape Town in 2002, 10% of children in the same schools had BLLs >10 µg/dl compared with 18% in 2007, [15] representing an 8% increase in BLLs, which may be due to the residual effects of past usage of leaded petrol, and leaded paint in homes, toys, playground equipment and informal industries. [5,14] It must also be noted that different methods were used to assess BLLs in 2002 compared with the 2007 survey; however, previous studies have found the LeadCare system to be comparable to formal laboratory analytical methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been found in other countries. [6,7,9] However, in Cape Town in 2002, 10% of children in the same schools had BLLs >10 µg/dl compared with 18% in 2007, [15] representing an 8% increase in BLLs, which may be due to the residual effects of past usage of leaded petrol, and leaded paint in homes, toys, playground equipment and informal industries. [5,14] It must also be noted that different methods were used to assess BLLs in 2002 compared with the 2007 survey; however, previous studies have found the LeadCare system to be comparable to formal laboratory analytical methods.…”
Section: Discussionmentioning
confidence: 99%
“…In resource-rich countries such as the USA, the average BLL for children is around 3 µg/dl, which is a significant decrease from levels found in the 1970s. [9] Nevertheless, BLLs as low as 3 µg/dl have been associated with adverse cognitive and behavioural outcomes in children. [7,[10][11][12] Widespread exposure to low levels of environmental lead may have a large public health impact, especially in resource-poor countries such as SA where resources to mitigate the adverse effects are limited, and where there are no blood lead surveillance and screening programmes.…”
mentioning
confidence: 99%
“…The CDC laboratory first analyzed samples with ICP-MS (Jones et al 2009) using a modification of a method of Nixon et al (1999) for analyses of metals in biological matrices. If sufficient blood remained, samples were then analyzed on LCII.…”
Section: Methodsmentioning
confidence: 99%
“…15 for having a blood lead concentration in excess of 5 μg/dL (50 ppb); 15% of US children who lived in housing units built before 1950 had a blood lead concentration ≥5 μg/dL (≥50 ppb), whereas 4.2% of children who lived in housing built between 1950 and 1978 had a blood lead concentration ≥5 μg/dL (≥50 ppb), compared with 2.1% of children who lived in housing units built after 1978. 27 No treatments have been shown to be effective in ameliorating the permanent developmental effects of lead toxicity. 28 Finally, the economic costs of childhood lead toxicity are substantial.…”
Section: Figurementioning
confidence: 99%
“…[43][44][45] Dust clearance tests, which involve collecting dust from floors or windows of a home by using a lead-free material that resembles a baby wipe, should be conducted after extensive repair, renovation, or abatement of older housing units to determine whether the housing intervention was sufficient to protect children from lead hazards, especially in housing units built before 1960. 27,34 Property owners are required to disclose possible presence of leadbased paint in properties built before 1978 and are required to provide the blue pamphlet from the EPA, HUD, and Consumer Product Safety Commission titled "Protect Your Family From Lead in Your Home" at the time of rental or sale.…”
Section: Lead In Paint and Dustmentioning
confidence: 99%